PENDAMPINGAN AKREDITASI PAUD DAN PNF DI KABUPATEN TULUNGAGUNG - Erfiana, Nita Agustina Nurlaila Eka (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2021)
Community participation in advancing education can be seen from the proliferation of establishment of PAUD and PNF institutions in the community. The application for accreditation is also carried out as an effort to obtain quality recognition from the government and the community. However, institutional managers often do not have enough information regarding the application procedure to improve the quality of the institution based on the accreditation criteria. This community service program is carried out in order to provide assistance to PAUD and PNF managers to apply for and obtain superior accreditation results. This program is intended for. The target of this activity is aimed at managers of PAUD institutions and other non-formal education institutions such as PKMB and LKP, especially those who do not yet have institutional accreditation or plan to reaccredit. This community service program is attended by representatives from 32 institutions, which are currently and will apply for accreditation https://colindancias.uvt.ro/. The mentoring process is carried out through seminars on urgency, stages, assessment criteria, and strategies for obtaining superior accreditation. As well as consulting assistance during the application process.